Wage-earning slaves : coartación in nineteenth-century Cuba - Varella, Claudia; Barcia Paz, Manuel, 1972- (University of Florida Press, 2020)
"This volume is the first systematic study of coartación, a process by which slaves worked toward purchasing their freedom in installments. Focusing on Cuba, this book reveals that instead of providing a "path to manumission," the process was often rife with obstacles that blocked slaves from achieving liberty"--